Is Month of Birth a Risk Factor for Colorectal Cancer? - N. K. Francis; N. J. Curtis; E. Noble; M. Cortina-Borja; E. Salib (Gastroenterology Research and Practice)
Introduction. The developmental origins of health and disease hypothesis and season of birth have been linked to a wide variety of later life conditions including cancer. Whether any relationship between month and season of birth and colorectal cancer exists is unknown. Methods. A case-control study was performed with month of birth extracted from a dedicated colorectal cancer database. Age and gender matched patients were used as a control group. Generalised linear models were fitted with Poisson and negative binomial responses and logarithmic links. A forward stepwise approach was followed adding seasonal components with 6- and 12-month periods. Results. 1019 colorectal cancer patients and 1277 randomly selected age and gender matched controls were included. For both men and women there is an excess of colorectal cancer in those born in autumn and a corresponding reduction of risk among those born in spring (p = 0.026). For the identified September peak, the excess risk for colorectal cancer was 14.8% (95% CI 5.6–32.3%) larger than the spring trough. Conclusion. There is a seasonal effect in the monthly birth rates of people who are operated for colorectal cancer with a disproportionate excess of cancer in those born in September. Further large studies are required to validate these findings.